Efek Pengendalian Internal dan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan: Studi Kasus Pada Perusahaan Daerah Air Minum Kota dan Kabupaten Sukabumi - Madani Muhammad Ibrahim; Idang Nurodin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research employs a quantitative method with the population consisting of Regional Water Companies in both Sukabumi City and Sukabumi Regency. The sampling technique used is purposive sampling, with a total of 51 respondents from both companies in Sukabumi City and Sukabumi Regency. The data used are primary data collected through the distribution of questionnaires. After the data was collected, the analysis was conducted using the SPSS 27 For Windows application, including data quality test, classical assumption test, multiple linear regression test, and hypothesis test. The research findings conclude that both aspects, namely internal control and accounting information systems, have a significant combined effect on the quality of financial reports. Additionally, separately, internal control and accounting information systems also have a significant effect on the quality of financial reports.